Micro-inverter for integrated grid-tie PV module using resonant controller - Gazoli, Jonas Rafael; Villalva, Marcelo Gradella [UNESP]; Siqueira, Thais G.; Ruppert, Ernesto (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Two-stage isolated converters for photovoltaic (PV) applications commonly employ a high-frequency transformer on the DC-DC side, submitting the DC-AC inverter switches to high voltages and forcing the use of IGBTs instead of low-voltage and low-loss MOSFETs. This paper shows the modeling, control and simulation of a single-phase full-bridge inverter with high-frequency transformer (HFT) that can be used as part of a two-stage converter with transformerless DC-DC side or as a single-stage converter (simple DC-AC inverter) for grid-connected PV applications. The inverter is modeled in order to obtain a small-signal transfer function used to design the PResonant current control regulator. A high-frequency step-up transformer results in reduced voltage switches and better efficiency compared with converters in which the transformer is used on the DC-DC side. Simulations and experimental results with a 200 W prototype are shown. © 2012 IEEE.
Keywords: AC-DC power converters; distributed power generation; modeling; photovoltaic systems; power transformers; pulse width modulation inverters; DC-AC inverters; Full-bridge inverters; Grid-connected PV; High frequency HF; High voltage; Low-voltage; MOSFETs; Photovoltaic; Photovoltaic systems; Pulse width modulation inverters; PV modules; Resonant controller; Single stage converters; Small-signal transfer functions; Step up transformers; Transformerless; Two-stage converter; DC transformers; Distributed power generation; Models; Power transformers; DC-DC converters